2019
DOI: 10.7717/peerj.7899
|View full text |Cite
|
Sign up to set email alerts
|

Identification of key genes and multiple molecular pathways of metastatic process in prostate cancer

Abstract: Background Cancer metastasis is well known as the most adverse outcome and the major cause of mortality in cancer patients, including prostate cancer (PCa). There are no credible predictors, to this day, that can reflect the metastatic ability of localized PCa. In the present study, we firstly identified the differentially expressed genes (DEGs) and molecular pathways involved in the metastaic process of PCa by comparing gene expressions of metastaic PCa with localized PCa directly, with the purpose of identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 41 publications
(42 reference statements)
3
9
0
Order By: Relevance
“…As an integrated analysis based on previous studies, our results showed partial overlap with those previously described. For example, consistent with previous investigations, FOS and FOXM1 were listed in the DEGs between metastatic PCa and localized PCa (Chandran et al 2007;Guo et al 2019). However, differences existed.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…As an integrated analysis based on previous studies, our results showed partial overlap with those previously described. For example, consistent with previous investigations, FOS and FOXM1 were listed in the DEGs between metastatic PCa and localized PCa (Chandran et al 2007;Guo et al 2019). However, differences existed.…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies reported that different gene expression profiles existed between metastatic PCa and localized PCa either in a single cohort (LaTulippe et al 2002;Varambally et al 2005;Chandran et al 2007;Taylor et al 2010) or in an integrated series (Liu et al 2018;Guo et al 2019;Xu et al 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the aging of the growing population, prostate cancer has become a main public health problem for men (Center et al, 2012). This tumor is often silent in clinical practice and usually found after it invades other tissues (Guo et al, 2019;Roobol & Carlsson, 2013;Shen & Abate-Shen, 2010). Studies of METTL3 in prostate cancer suggest that it is a oncogene.…”
Section: Prostate Cancermentioning
confidence: 99%
“…Despite initial effective responses with androgen suppression therapy (AST), almost all patients ultimately progress to metastatic castration-resistant prostate cancer (mCRPC) [12,13]. Docetaxel, abiraterone, cabazitaxel, and (Sip-T) are approved by the FDA for the treatment of mCRPC, however each of these regimens provides only limited 2-4 months median survival bene t [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%